Addiction, Choice and Criminal Law - Morse, Stephen J. (2017)
This chapter is a contribution to a volume, Addiction and Choice, edited by Nick Heather and Gabriel Segal that is forthcoming from Oxford University Press. Some claim that addiction is a chronic and relapsing brain disease; others claim that it is a product of choice; yet others think that addictions have both disease and choice aspects. Which of these views holds sway in a particular domain enormously influences how that domain treats addictions. With limited exceptions, Anglo-American criminal law has implicitly adopted the choice model and a corresponding approach to responsibility. Addiction is irrelevant to the criteria for the prima facie case of crime, it is not an excusing or mitigating condition per se, and it does not contribute relevant evidence to existing excusing conditions, such as legal insanity. This chapter evaluates the criminal law’s model of responsibility using scientific and clinical evidence and dominant criminal law theories. It concludes that although the law’s approach is generally justifiable, current doctrine and practice are probably too unforgiving and harsh. Recommendations for reform conclude the chapter